Influence of the Game Context and Levels of Physical Activity on the Behavior of Basketball Coaches - López-Laval; Scanlan A.T; Sitko S; Vaquera-Jiménez A. (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
Coaches can exert a significant influence on players and games. The aim of this study is to assess behavior in the form of heart rate (HR) responses and distance traveled of basketball head coaches during matches considering the different match contexts faced as a score differences and time outs during the game direction and levels of physical activity and coaches experience. Four basketball head coaches are recruited in this case report. Mean and maximal absolute and relative HR are determined across matches. Scoring streaks (±6 consecutive points) and time outs are considered as influence value. The in-match distance traveled measured using microsensors, coaching experience, and daily activity on HR responses is also determined. Higher HR are evident across matches compared to periods prior to and following matches. HR is significantly (P <.05) elevated during later time-outs compared to earlier time-outs, with positive scoring streaks yielding a tendency towards higher HR compared to negative and no scoring streaks. Experience (rs = -0.91, P <.001), daily activity levels (rs = -0.83, P <.001), and weekly METS (rs = -0.78, P =.002) are negatively associated with match HR, while in-match distance (rs = 0.69, P =.013) is positively associated with match HR. These data indicate that matches elevate the cardiovascular stress imposed on basketball head coaches, with later time-outs and positive scoring streaks promoting heightened HR. Moreover, in-match activity and personal characteristics (less experience and lower physical activity) further augment match HR in coaches.